2013
DOI: 10.1136/emermed-2012-201463
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Pentax-AWS in performing tracheal intubation while wearing chemical, biological, radiation and nuclear personal protective equipment: a randomised crossover trial using a manikin

Abstract: Although the CBRN-PPE adversely affected time required to complete tracheal intubation with the AWS, suited intubations using the AWS were even superior to unsuited intubations using the McL. The AWS should be a promising device to perform tracheal intubation while wearing the CBRN-PPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…We included 22 manikin studies (42 trials) . The Pentax AWS was more effective than the Macintosh laryngoscope for all outcomes except the rate of audible dental clicks or significant dental compression (equivalent to oral or pharyngeal injury in human studies, Table ).…”
Section: Resultsmentioning
confidence: 99%
“…We included 22 manikin studies (42 trials) . The Pentax AWS was more effective than the Macintosh laryngoscope for all outcomes except the rate of audible dental clicks or significant dental compression (equivalent to oral or pharyngeal injury in human studies, Table ).…”
Section: Resultsmentioning
confidence: 99%
“… 11 A previous study of the use of a Pentax-AWS video laryngoscope in a CBRN-PPE scenario has shown that suited intubation with a Pentax-AWS can be performed in a shorter period of time than unsuited intubation with an MAC. 12 …”
Section: Discussionmentioning
confidence: 99%
“… 10 11 However, there is little current evidence for or against the use of videolaryngoscopy when wearing chemical protective equipment (CPE). 12 13 The aim of the current small, unblinded, pilot study is to describe the performance characteristics of various laryngoscopic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…performed all over the world, the United Kingdom (10), [19][20][21][22][23][24][25][26][27][28] Israel (6), [29][30][31][32][33][34] and the United States (5) 15,[35][36][37][38][52][53][54] ,published the majority of the studies. Australia (3), [39][40][41] South Africa (2), 42,43 Canada (1), 44 France (1), 45 and South Korea (1) 46 published the rest. Only 3 (10%) of the studies were performed by military organizations.…”
Section: Cbrn-ppe Effects On Medical Device Use During Emergency Respmentioning
confidence: 99%